Diagnostic accuracy of the A-test and cutoff points for assessing outcomes and planning acute and post-acute rehabilitation of patients surgically treated for hip fractures and osteoarthritis - Vukomanović, Aleksandra S; Djurović, Aleksandar; Brdareski, Zorica (Vojnosanitetski pregled, 2017)
Background/Aim. The A-test is used in daily clinical practice for monitoring functional recovery of orthopedic patients during early rehabilitation. The aim of this study was to determine the accuracy of A-test and cutoff point at which the test can separate patients with and without functional disability at the end of early rehabilitation. Also, it was important to determine whether A-test has that discriminative ability (and at which cutoff points) in the first days of early rehabilitation in order to have time to plan post acute rehabilitation. Methods. This measurement-focused study was conducted in the Orthopedic Ward during early inpatient rehabilitation (1st−5th day after the operation) of 60 patients with hip osteoarthritis (HO) that underwent arthroplasty and 60 surgically treated patients with hip fracture (HF). For measurements we used the A-test and the University of Iowa Level of Assistance Scale (ILAS) as the gold standard. For statistical analysis we used the receiver operating characteristic (ROC) curve and the area under the curve (AUC) with 95% confidence interval for the results of A-test from the first to the fifth day of rehabilitation, sensitivity, specificity, the rate of false positive and false negative errors, positive and negative predictive value, ratio of positive and negative likelihood ratio, accuracy, point to the ROC curve closest to 0.1 and Youden index for all the cutoff points. Results. The AUC was 0.825 (0.744−0.905) for the first day of rehabilitation, 0.922 (0.872−0.972) for the second day of rehabilitation, 0.980 (0.959−1.000) for the third day of rehabilitation, 0.989 (0.973−1.004) for the fourth day, and 0.999 (0.996−1.001) for the fifth day of rehabilitation. The optimal cutoff for the results of A-test was: 7/8 for the first day, 29/30 for the fourth day, and 34/35 for the fifth day of rehabilitation. On the second and the third day A-test had two cutoff points, the lower point safely separated the patients with functional disability, while the upper point ruled out functional disability. On the 2nd rehabilitation day the cutoff points were 12/13 and 17/18, on the 3rd rehabilitation day cutoff points were 13/14 and 18/19. Conclusion. The A-test has all characteristics of an accurate tool which can be used for separating patients with and without functional disability at all stages of early rehabilitation after surgically treated hip disease or fracture. Based on the results of A-test within the first days of early rehabilitation, it is possible to make a plan for postacute rehabilitation.
Keywords: rehabilitation; recovery of function; hip prosthesis; postoperative period; predictive value of tests; serbia